Kit Carson Inn Specializing in Steaks & Mexican Food (Cimarron, New Mexico Cimarron Legend, 1992)
Advertisement for Kit Carson Inn in Cimarron, New Mexico.
Master List item # 42
File location is in the Raton File Cabinet
Keywords: Kit Carson Inn; Philmont Scout Ranch; La Mesa Park; Restaurant; Croquet Courts; Horse Shoes; Swimming; Air Conditioning; Telephone; Satellite TV; RV Park; Historical Photos & Mount Gallery; Cocktail Lounge; Cimarron, New Mexico